DOAS Calibration Technique for SO2 Emission Measurement Based on H2SO4 and Na2SO3 Reaction - Januar Arif Fatkhurrahman; Ikha Rasti Julia Sari; Yose Andriani; Moh Syarif Romadhon; Nur Zen; Adi Prasetio; Ali Murtopo Simbolon (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2020)
The coal used as a primary fuel in an Indonesian power plant produces sulfur dioxide emission from its burning process. Several testing and monitoring methods developed, from laboratory analysis, CEMs based instrument, and absorption spectroscopy method developed for this purpose. Differential Optical Absorption Spectroscopy (DOAS) method based on Lambert-Beer law used as emission quantification. DOAS instrumentation developed in this research to measure sulfur dioxide as one of the emission parameters. Sulfur dioxide generated from the reaction between the sulfuric acid and dilute sodium sulfite. CCD spectrometer used to measure sulfur dioxide spectrum intensity at 260 to 350 nm absorption cross-section. There is a high correlation between sulfur dioxide gas produced by that reaction to spectrum intensity, with coefficient determination (r2) 0.9783, 0.9822, 0.9866, 0.9928 or coefficient correlation (r) 0.989, 0.991, 0.993, and 0.996 from lowest range concentration to highest range concentration. Precision analysis from gas calibration standard using Horwitz ratio indicates instrument setup precise enough with 0.504 Horwitz ratio, according to its acceptable range. The suspended particulate matter may interfere with UV penetration into CCD detector in emission simulation test using gasoline generator exhaust that causes 2.5 times deviation error between typical 800 ppm concentrated sulfur dioxide from chemical reaction and gasoline generator exhaust.